The Coca Plant: Gendered Conversations with a Totemic Persona - Böschemeier, Ana Gretel Echazú; Flores, Maria Eugenia (Kalágatos, 2024)
This article explores how the Coca plant [Erythroxylum coca], despite its persecution in Americas since the XVIth Century and its criminalization during the “War on Drugs” in the XXth Century, remains a key interlocutor for Indigenous and rural communities in South America, with a focus in the Andean highlands. Viewing Coca as a persona involves understanding it within a complex web of totemic entanglements and plural ontologies. In the Andes, interpretations of Coca emphasize gendered interconnectedness rather than an essential femininity. Coca's gendered agency manifests itself in social, therapeutic, and spiritual practices, reinforcing meaningful conversations between human and nonhuman beings.